Postoperative Onset and Detection of SARS-CoV-2 in Surgically Resected Specimens From Gastrointestinal Cancer Patients With Pre/Asymptomatic COVID-19. Issue 6 (December 2020) - Liu, Yan-Liang; Ren, Jun; Yuan, Jing-Ping; Zhang, Zhi-Jiang; Guo, Wen-Yi; Guan, Yang; Moeckel, Gilbert; Ahuja, Nita; Fu, Tao
Abstract : Objective: To describe the epidemiologic features and clinical courses of gastrointestinal cancer patients with pre/asymptomatic COVID-19 and to explore evidence of SARS-CoV-2 in the surgically resected specimens. Summary Background Data: The advisory of postponing or canceling elective surgeries escalated a worldwide debate regarding the safety and feasibility of performing elective surgical procedures during this pandemic. Limited data are available on gastrointestinal cancer patients with pre/asymptomatic COVID-19 undergoing surgery. Methods: Clinical data were retrospectively collected and analyzed. Surgically resected specimens of the cases with confirmed COVID-19 were obtained to detect the expression of ACE2 and the presence of SARS-CoV-2. Results: A total of 52 patients (male, 34) with a median age 62.5 years were enrolled. All the patients presented no respiratory symptoms or abnormalities on chest computed tomography before surgery. Six patients (11.5%) experienced symptom onset and were confirmed to be COVID-19. All were identified to be preoperatively pre/asymptomatic, as 5 were with SARS-CoV-2 presenting in cytoplasm of enterocytes or macrophages from the colorectal tissues and 1 had symptom onset immediately after surgery. The case fatality rate in patients with COVID-19 was 16.7%, much higher than those without COVID-19 (2.2%). Conclusions: Gastrointestinal cancer patients with pre/asymptomatic COVID-19 were at high risk of postoperative onset and death. At current pandemic, elective surgery should be postponed or canceled. It highlights the need for investigating the full clinical spectrum and natural history of this infection. The early colorectal tropism of SARS-CoV-2 may have major implications on prevention, diagnosis, and treatment of COVID-19. Abstract : Supplemental Digital Content is available in the text